Object-Oriented Programming: Foundations, Evolution, and Industrial Applications - Keyri Daniela Sánchez Durán (Asian Journal of Science, Technology, Engineering, and Art, 2026)
Although Object-Oriented Programming (OOP) is widely adopted, a consolidated review that systematically analyzes its foundational principles, historical evolution, industrial applications, and inherent limitations remains valuable for new developers and practitioners. This study aims to analyze and comprehensively understand the fundamentals of OOP, highlighting its relevance and applications in contemporary software development. A documentary research approach was employed using systematic literature analysis to synthesize core concepts, major historical milestones, and practical industry applications, based on academic and technical sources examined through descriptive and comparative analysis. The findings indicate that OOP rests on four key principles: encapsulation, inheritance, polymorphism, and abstraction, and that the paradigm evolved historically from its early emergence in Simula in the 1960s to its consolidation in languages such as Java in 1995, followed by its expansion through modern languages including Python and C#. In practice, OOP is critically applied in diverse domains such as video game development, corporate software systems (e.g., ERP and CRM), and Artificial Intelligence, where modular design and code reuse are essential. The study concludes that OOP principles enable the creation of modular, reusable, and scalable systems that are crucial for addressing contemporary software complexity, despite challenges such as a steep learning curve and the need for meticulous design and planning. The implications of this research include theoretical contributions to the understanding of foundational programming paradigms and practical recommendations for adopting a structured, object-centric design philosophy in software development.